1997
DOI: 10.1007/bf02436968
|View full text |Cite
|
Sign up to set email alerts
|

Laser emission from dye-doped organic-inorganic particles of microcavity structure

Abstract: Abstract. Interaction between laser light and a micrometer-size spherical particle causes an optical resonance in its interior since a spherical wall acts as a cavity. The present work seeks to investigate the preparation of organicinorganic particles containing laser dyes and demonstrate their lasing behavior. Rhodamine 6G was incorporated into organic-inorganic spherical particles of micrometer-size using sol-gel technique. Phenyl triethoxy silane was used as a starting material for particles. Particle size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…7 Shibata et al prepared rhodamine 6G-doped PhSiO 32 particles using the two-step acid-base catalyzed sol-gel process and demonstrated their lasing behavior. 8 Hah et al demonstrated a simple preparation process of hollow particles using the PhSiO 32 particles prepared by the two-step acid-base catalyzed process. 9 We reported preparation of PhSiO 32 particles using the two-step acid-base catalyzed sol-gel process and found that the PhSiO 32 particles showed glass transition behavior.…”
Section: -14mentioning
confidence: 99%
See 1 more Smart Citation
“…7 Shibata et al prepared rhodamine 6G-doped PhSiO 32 particles using the two-step acid-base catalyzed sol-gel process and demonstrated their lasing behavior. 8 Hah et al demonstrated a simple preparation process of hollow particles using the PhSiO 32 particles prepared by the two-step acid-base catalyzed process. 9 We reported preparation of PhSiO 32 particles using the two-step acid-base catalyzed sol-gel process and found that the PhSiO 32 particles showed glass transition behavior.…”
Section: -14mentioning
confidence: 99%
“…Results of that study indicated that the parti- cle size was altered according to the stirring speed. 8 In the present study, we used a solvent and fixed the stirring speed at c.a. 1300 rpm, but the particle size was also varied by the concentration of PhSi OEt 3 in a starting solution.…”
mentioning
confidence: 99%
“…In particular, as for microencapsulation of functional organic dyes, it is expected to be applied to, for example, display materials, information-recording materials, microsphere lasers, biomaterials such as drug delivery system and in-vivo fluorescent dye materials, and it is a field in which great development is expected in the future [1][2][3][4][5][6][7][8][9][10][11][12][13]. Conventionally, MCs of functional organic dyes have a structure in which an organic dye forms a core that is encased by an organic-polymer shell.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the low durability of the dye, such MCs have been insufficient in terms of performance. Although organic pigments with good durability have been used, they are not soluble in a solvent, so it is difficult to make them into microparticles and microencapsulate them, and good performance has not been achieved [8]. In general, mechanical pulverization by a bead mill or the like is mainly used for micronizing an organic pigment [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…By the technique, particles of various sizes from submicron to several ten micrometer were made at once. Particles of 4-'6 tm in diameter were selected and from them, a strong laser emission peak at 598 nm was confirmed by pumping a laser light of 532 nm wavelength with a second harmonic pulse of Q-switched Nd-YAG laser [7].…”
Section: Introductionmentioning
confidence: 99%